Pengaruh Kombinasi Pupuk NPK Terhadap Produksi Kacang Tanah di Daerah Transmigrasi SP1 Prafi, Kabupaten Manokwari - Y. S. Budiyanto (Fakultas Pertanian Universitas Papua, 2009)
The object of this study was to find out the best combination of Urea, SP36 and KCl fertilizer to increase peanut yield at SP1 Transmigration Area, Prafi district, Manokwari.The completely randomized design was used in this experiment which consist of five combinations of NPK fertilizer treatment and none fertilizer treatment as a control, in three replications. Urea, SP36 and KCl were used as source of NPK fertilizer.The result showed that fertilizers combination treatment gave better results in all variables observed compare to none fertilizer treatment, except the number of pod per plant. Whatever the fertilizer combination used would give significantly bigger size grain compare to none fertilizer treatment.The fertilizer combination of 100 kg Urea, 75 kg SP36 and 60 kg KCl was the best combination which could be applicated at SP1 area, Prafi district, Manokwari because it seemed to have the best yield among all combination treatments and gave dry grain weight per plot for about 3.43 kg or equivalent to 1.71 ton per hectar.